2020
DOI: 10.3390/biom10030469
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathognomonic Biomarker PrPSc and the Contribution of Cell Free-Amplification Techniques to the Diagnosis of Prion Diseases

Abstract: Transmissible spongiform encephalopathies or prion diseases are rapidly progressive neurodegenerative diseases, the clinical manifestation of which can resemble other promptly evolving neurological maladies. Therefore, the unequivocal ante-mortem diagnosis is highly challenging and was only possible by histopathological and immunohistochemical analysis of the brain at necropsy. Although surrogate biomarkers of neurological damage have become invaluable to complement clinical data and provide more accurate diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 343 publications
(366 reference statements)
0
5
0
Order By: Relevance
“…Other potential biomarkers, such as blood, urine, and saliva, have also been investigated for their potential use in diagnosing and monitoring sCJD. One potential biomarker is the prion protein, which can be detected in blood (54). However, the sensitivity and specificity of this method are currently not high enough for clinical use.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
“…Other potential biomarkers, such as blood, urine, and saliva, have also been investigated for their potential use in diagnosing and monitoring sCJD. One potential biomarker is the prion protein, which can be detected in blood (54). However, the sensitivity and specificity of this method are currently not high enough for clinical use.…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
“…These assays have a rather low sensitivity and cannot be performed in live animals. In recent years, in vitro prion-replication assays, including PMCA and RT-QuIC, have been extensively used to detect prions in biological fluids of different animal species, including CWD [ 113 , 114 , 115 , 116 , 117 , 118 ]. These assays rely on mimicking in vitro the mechanism of prion replication to amplify minute amounts of PrP Sc at expenses of large quantities of PrP C using a cyclic-amplification procedure involving cycles of incubation and fragmentation.…”
Section: Strategies For Minimizing Cwd Spreading: Is Eradication Of C...mentioning
confidence: 99%
“…ThT binds to cross-β structures, thus detecting oligomers and fibrils that are in the amyloid conformation [ 66 ]. PMCA and RT-QuIC protocols are routinely employed for detection of the PrP-based prion in the meat and body liquids of domestic animals, as well as in natural environments [ 67 ]. RT-QuIC protocol for the detection of PrP aggregates in CSF has also been implemented into clinical practice for diagnostics of sporadic CJD in humans by The National CJD Research & Surveillance Unit (NCJRSU) in UK, and demonstrated 92% sensitivity and 100% specificity [ 68 ].…”
Section: Techniques Based On Amplification Of Misfolded Protein Conformationsmentioning
confidence: 99%